Factors influencing multi-disciplinary tumor board recommendations in stage III non-small cell lung cancer. (February 2021) - Ronden, Merle I.; Bahce, Idris; Hashemi, Sayed M.S.; Dickhoff, Chris; de Haan, Patricia F.; Becker, Annemarie; Spoelstra, Femke O.B.; Dahele, Max R.; Ali, Rania; Tiemessen, Marian A.; Tarasevych, Svitlana; Maassen van den Brink, Karen; et al.
Highlights: MDT decision-making for stage III NSCLC was studied between 2015–2017. Surgery or chemo-radiotherapy were recommended in just 61 % of patients. Deaths from NSCLC at ≤2 years were seen in 41–43 % after all treatments. Better tolerated and more effective treatments are needed in stage III NSCLC. Abstract: Objectives: Treatment patterns in patients with stage III non-small cell lung cancer (NSCLC) vary considerably between countries, for reasons that are not well understood. We studied factors influencing treatment decision-making at thoracic multidisciplinary tumor boards (MDT's) and outcome for patients treated between 2015–2017, at a regional network comprising 5 hospitals. Materials and methods: Details of all patients, including comorbidities, with stage III NSCLC were collected in an ethics-approved database. Weekly MDT's were conducted. The preferred radical intent treatments (RIT) for suitable patients were assumed to be concurrent chemoradiotherapy and/or surgery and other therapies were non-radical intent treatments (n-RIT). Results: Of 197 patients identified, 95 % were discussed at an MDT. RIT were recommended in 61 % of patients, but only 48 % finally received RIT. The estimated median OS was significantly better for patients undergoing RIT (28.3 months, CI-95 % 17.3–39.3), versus those who did not (11.2 months, CI-95 % 8.0−14.3). Patient age ≥70 years and a WHO-PS ≥2 were the most important predictors of not recommending RIT. Deaths due to progressive lung cancer within 2 years were observed in 36, 26 and 29 % of patients who received RIT, sequential chemoradiotherapy or radical radiotherapy. Corresponding comorbidity related deaths within 2 years were 3, 12 and 38 %. Conclusion: A large number of patients who underwent MDT review were considered too old or not fit for RIT. More effective and better tolerated systemic treatments are required for patients presenting with stage III NSCLC.